Pelatihan Pengelolaan Sampah Organik Ibu-Ibu PKK di Perumahan Reny Jaya RT 04 RW 07 Kelurahan Pondok Petir Kecamatan Bojong Sari Depok - Madonna, Sandra; Nursetyowati, Prismita; Hermiyetti (LPkM Universitas Bakrie, 2019)
Pondok Petir Village is the largest population in Bojongsari Subdistrict, Depok. The most prominent land use in this village is for housing. Reny Jaya Housing is one of the largest housing complexes in Pondok Petir. The large population and diversity of these activities contribute to increasing the number and problem of waste. Organic waste originating from households dominates waste generation in Indonesia. The production of organic waste in Pondok Petir Village has the potential to be managed well. The composting method using Takakura basket and processing cooking oil into soap is very appropriate to be introduced as a proper technology in processing organic waste from households. The problem that is happening right now is that community participation is still not well-directed and well-organized; there is still a lack of community sanctity towards the waste problem. The potential for household waste to be processed can even be of economic value. However, it has not been maximally implemented because there is still a lack of motivation and insight from the community in managing waste. The Waste Management Training Activity has been carried out, attended by 16 participants consisting of homemakers in RT 04 RW 07 Pondok Petir Village, Depok. With the method of presentation in presentation, the practice of making Takakura composter, making washing soap from used cooking oil, as well as discussion and question and answer. This household-scale waste management training is expected to increase community involvement in the Pondok Petir Village in managing their waste and can socialize and motivate other households in the vicinity so that it can become one of the examples of areas that are clean, healthy, and free of rubbish.